2021
DOI: 10.1161/circulationaha.121.054516
|View full text |Cite
|
Sign up to set email alerts
|

Social Vulnerability and Premature Cardiovascular Mortality Among US Counties, 2014 to 2018

Abstract: Background: Substantial differences exist between United States counties with regards to premature (<65 years of age) cardiovascular disease (CVD) mortality. Whether underlying social vulnerabilities of counties influence premature CVD mortality is uncertain. Methods: In this cross-sectional study (2014–2018), we linked county-level CDC/ATSDR SVI (Centers for Disease Control and Prevention/Agency for Toxic Substances and Disease Registry Social Vulne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 31 publications
5
68
0
Order By: Relevance
“…The American Heart Association considers education, income, employment status, social networks, and access to medical care or other health-promoting resources (often associated with disparate access by race and ethnicity) as major determinants of cardiovascular risk and health ( 1 ). Disparities across these categories are well described ( 2 ), with Black Americans two to three times as likely as White Americans to die of preventable heart disease. Despite overall declines in mortality ( 3 ), an >19,000 excess Black deaths from heart disease across the 50 largest U.S cities occur annually ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The American Heart Association considers education, income, employment status, social networks, and access to medical care or other health-promoting resources (often associated with disparate access by race and ethnicity) as major determinants of cardiovascular risk and health ( 1 ). Disparities across these categories are well described ( 2 ), with Black Americans two to three times as likely as White Americans to die of preventable heart disease. Despite overall declines in mortality ( 3 ), an >19,000 excess Black deaths from heart disease across the 50 largest U.S cities occur annually ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, environmental research focused primarily on behavioral factors, such as inactivity and diet. However, in recent years, cardiometabolic risk was linked to various environmental components, including the social environment 5,6 , environmental pollutants 3,7 , and, more specifically, air pollution [8][9][10][11][12][13] . A recent meta-analysis concluded that each ten µg/m 3 increase in long-term fine particulate matter (PM 2.5 ) exposure was associated with an 8% increase in T2D prevalence risk, and each ten µg/m 3 increase in long-term nitrogen dioxide (NO 2 ) exposure was associated with a 7% increase in T2D prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of proper access to health care and healthy choices (example, food deserts) can vary depending on a person's zip code and can result in health disparities. 14 For example, the southwestern and southeastern parts of the United States have the largest concentration of counties with social vulnerabilities and CVD mortality. Counties with higher social vulnerability index have a significantly higher mortality attributable to CVD and Black individuals in each social vulnerability index category had higher age‐adjusted CVD mortality compared with White individuals.…”
mentioning
confidence: 99%